2023
DOI: 10.1021/acs.jproteome.3c00199
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Protein Biomarker Discovery in CLN3

Abstract: is a fatal, pediatric, neurodegenerative disease caused by variants in CLN3, which encodes the endolysosomal transmembrane CLN3 protein. No approved treatment for CLN3 is currently available. The protracted and asynchronous disease presentation complicates the evaluation of potential therapies using clinical disease progression parameters. Biomarkers as surrogates to measure the progression and effect of potential therapeutics are needed. We performed proteomic discovery studies using cerebrospinal fluid (CSF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Prospective protein profiling of CSF from LP from 27 preterm infants showed that the proteome can predict neurodevelopmental outcomes [30]. In the proteomic study of CSF from children with the syndromic CLN3-Batten, a fatal neurodegenerative disease caused by mutations in the endolysosomal transmembrane CLN3 protein, a protein implicated in axonal development, were identified as candidate biomarkers [31].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective protein profiling of CSF from LP from 27 preterm infants showed that the proteome can predict neurodevelopmental outcomes [30]. In the proteomic study of CSF from children with the syndromic CLN3-Batten, a fatal neurodegenerative disease caused by mutations in the endolysosomal transmembrane CLN3 protein, a protein implicated in axonal development, were identified as candidate biomarkers [31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was proposed that these genes can provide fresh clinical data that can be applied to the diagnosis and effective therapy of IBD ( 73 ). Although the mechanisms through these genes cause disease are unclear, FAM217B has been identified as a protein biomarker for syndromic CLN3-Batten ( 116 ). In addition, differentially expressed RIBC2 is a prognostic biomarker in cervical cancer ( 117 ).…”
Section: Roles Of Dnam In Ibdmentioning
confidence: 99%